Spirit of Entrepreneurial and Innovative as the Main Capital Competition for Creative Industry Center Sasirangan South Kalimantan - Fathulliansyah, Noor; Loupias, Henry H. (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
The United Nations has designated 2021 as the International Year of the Creative Economy for Sustainable Development. Indonesia's creative economy contributes IDR 1,211 trillion (7.4%) to the national GDP and employs 14.3% of its workforce. There are 3 leading sub-sectors, namely crafts, culinary, and fashion. The creative industry is a new engine of world economic growth which is developing the most rapidly. Sasirangan Kampong in Banjarmasin City, South Kalimantan, is a center for the creative industry of Sasirangan traditional pattern clotch. Sasirangan cloth is one of the creative economic potentials of the local community. The research method used is descriptive-analytical, which is to describe the subject and conduct an in-depth analysis. Its main objective is to examine the entrepreneurial and innovative practices of entrepreneurs and craftsmen. The findings show that most of entrepreneurs have high entrepreneurial spirit so they can survive and compete. The craftsmen innovate products and processes to create new motifs, processes and new techniques that can differentiate their products in the market. However, entrepreneurship and innovation are the main assets in the competitive fashion creative industry.